SISTEM KONTROL OTOMATIS LAMPU DENGAN PHOTODIODE MENGGUNAKAN RANGKAIAN KOMPARATOR IC UA741 - Nurfauziah, Aulia; Febrian Anwar, Syahid; Rizki Amiruddin, Ahmad; Asrila; Amri, Fauzan; Kurnianingtyas, Rahajeng (JURNAL REKAYASA ENERGI, 2025)
This research presents the design and implementation of an automatic lamp control system using a photodiode sensor and an IC UA741 comparator circuit. The aim is to develop a system capable of responding to changes in light intensity in real-time to control the ON/OFF state of the lamp. The method involves designing a light detection circuit with a photodiode, signal conditioning, and voltage comparison using the UA741 comparator. Experimental results show that the output voltage of the photodiode is directly proportional to the incident light intensity. During testing, a maximum voltage of 3.6 V was recorded when the photodiode was exposed to light from 5 LEDs, with the voltage decreasing as the number of light sources was reduced. The system successfully switches the lamp on automatically when the light intensity falls below a defined threshold and switches it off when the light exceeds this threshold. This design offers an energy-efficient lighting control system with simple architecture, low cost, and high responsiveness, making it suitable for household applications or small public areas.